2004
DOI: 10.1099/vir.0.80403-0
|View full text |Cite
|
Sign up to set email alerts
|

Replication, recombination and packaging of amplicon DNA in cells infected with the herpes simplex virus type 1 alkaline nuclease null mutant ambUL12

Abstract: The alkaline nuclease (AN) encoded by gene UL12 of herpes simplex virus type 1 (HSV-1) is essential for efficient virus replication but its role during the lytic cycle remains incompletely understood. Inactivation of the UL12 gene results in reductions in viral DNA synthesis, DNA packaging, egress of DNA-containing capsids from the nucleus and ability of progeny virions to initiate new cycles of infection. Mechanistically, AN has been implicated in resolving branched structures in HSV-1 replicative intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The phenotype of UL12 mutants is complex. We previously reported that the UL12-null virus, AN-1, was compromised for growth on nonpermissive cells, with viral yields 2 to 3 logs lower than that of wild-type virus (33)(34)(35)55). In this paper, we show that the growth defect of AN-1 in nonpermissive cells is even more serious than previously recognized.…”
Section: Discussionmentioning
confidence: 52%
“…The phenotype of UL12 mutants is complex. We previously reported that the UL12-null virus, AN-1, was compromised for growth on nonpermissive cells, with viral yields 2 to 3 logs lower than that of wild-type virus (33)(34)(35)55). In this paper, we show that the growth defect of AN-1 in nonpermissive cells is even more serious than previously recognized.…”
Section: Discussionmentioning
confidence: 52%
“…UL12 is another HSV-1 protein with a nuclease motif and for which nuclease activity has been confirmed. UL12 may play a role in resolving X and Y DNA structures arising during viral DNA replication and in encapsidation (32). Nuclease activity has not yet been reported for UL24; however, the discovery that the motif is important for the function of the protein suggests that UL24 may indeed possess a nuclease function.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of baby hamster kidney 21 clone 13 (BHK) cells and preparation of stocks of wild-type (wt) HSV-1, strain 17 syn + , were as described previously (Porter & Stow, 2004). Rabbit skin cells were grown in Dulbecco's modified Eagle's medium containing 10 % fetal calf serum, 100 U penicillin ml −1 and 100 Όg streptomycin ml −1 .…”
Section: Methodsmentioning
confidence: 99%